"KELUAR DARI PRINSIP DERAJAT KEKERABATAN DALAM FIQH MAWARIS " - Ahmad Jalaludin (Jurnal Hukum Islam, 2013)
In the fiqh of maharis, a relative in principle prevented from obtaining an inheritance if there are other relatives with degrees his kinship with the heir is higher (closer). this principle it is felt that it does not provide justice to relatives who are parents died before the heir. Compilation of Islamic Law in Indonesia adopted relocation as a partial measure giving inheritance to relatives whose parents have died before the heir. In its development, the Court Agung made changing places a part that was no longer there partial part of the Islamic inheritance system that he built. With steps This is the principle of the degree of kinship which is considered as something established in the Maharis fiqh has become neglected.